2007
DOI: 10.1051/medsci/20072389756
|View full text |Cite
|
Sign up to set email alerts
|

Régime méditerranéen et ostéoporose

Abstract: L'ostéoporose et, en conséquence, le nombre de fractures ostéoporotiques, devraient connaître une augmentation considérable du fait du vieillissement de la population. Ainsi, en France, on estime que le nombre de fractures du col du fémur triplera entre 1990 et 2025 [1].L'ostéoporose, un problème physiopathologique lié au vieillissement L'ostéoporose, affection diffuse du squelette, se caractérise par une masse osseuse réduite associée à des altérations microarchitecturales, conduisant à une augmentation de la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…This effect has been mainly attributed to specific eating pattern [13, 14]. The term “Mediterranean Diet” is currently used in the literature to indicate the traditionally dietary habits of the people living in countries bordering the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This effect has been mainly attributed to specific eating pattern [13, 14]. The term “Mediterranean Diet” is currently used in the literature to indicate the traditionally dietary habits of the people living in countries bordering the Mediterranean Sea.…”
Section: Discussionmentioning
confidence: 99%
“…Its increased consumption is reflected in the high monounsaturated to saturated fatty acid and has been found to be associated with a reduced prevalence of risk factors for major chronic inflammatory diseases included osteoporosis [7, 13, 21]. Adherence to MD has been associated with higher BMD and has been shown to prevent bone disease [9, 13, 14, 22–24]. The Framingham Osteoporosis Study Cohorts previously showed that a dietary pattern similar to MD was predictive of greater BMD in adults [22].…”
Section: Discussionmentioning
confidence: 99%
“…Following the EVOS study [17], which highlighted the importance of diet, particularly dairy products, in preventing osteopo-rosis, other studies investigated the effects of other substances that are rich in vitamins and minerals with antioxidant and alkaline effects and showed that these foods are associated with the achievement of higher peak bone mass during adolescence and less rapid loss of bone density after menopause [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Elles induisent notamment une neurogenèse plus importante dans l'hippocampe [7], structure cérébrale essentielle dans les pro- Tout le monde n'est malheureusement pas logé à la même enseigne. Certains sujets ont la chance d'avoir une profession où ils s'épanouissent, peu ou pas de facteurs de risque vasculaire, une alimentation de type méditerra-néen [11] …”
Section: Jean-françois Dartiguesunclassified